Cu2In alloy-embedded ZrO2 catalysts for efficient CO2 hydrogenation to methanol: promotion of plasma modification - Song, Fujiao; Gao, Jia; Yang, Bairen; Cao, Yan; Liu, Huanhuan; Xu, Qi (Frontiers in Chemistry, 2023)
Cu1In2Zr4-O-C catalysts with Cu2In alloy structure were prepared by using the sol–gel method. Cu1In2Zr4-O-PC and Cu1In2Zr4-O-CP catalysts were obtained from plasma-modified Cu1In2Zr4-O-C before and after calcination, respectively. Under the conditions of reaction temperature 270°C, reaction pressure 2 MPa, CO2/H2 = 1/3, and GHSV = 12,000 mL/(g h), Cu1In2Zr4-O-PC catalyst has a high CO2 conversion of 13.3%, methanol selectivity of 74.3%, and CH3OH space-time yield of 3.26 mmol/gcat/h. The characterization results of X-ray diffraction (XRD), scanning electron microscopy (SEM), and temperature-programmed reduction chemisorption (H2-TPR) showed that the plasma-modified catalyst had a low crystallinity, small particle size, good dispersion, and excellent reduction performance, leading to a better activity and selectivity. Through plasma modification, the strong interaction between Cu and In in Cu1In2Zr4-O-CP catalyst, the shift of Cu 2p orbital binding energy to a lower position, and the decrease in reduction temperature all indicate that the reduction ability of Cu1In2Zr4-O-CP catalyst is enhanced, and the CO2 hydrogenation activity is improved.